2015
DOI: 10.1017/s0031182015000694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toxocara larvae on brain cell survival by in vitro model assessment

Abstract: Neuroinvasive larvae of the common dog and cat roundworms, Toxocara canis and Toxocara cati, may cause severe neurological and neuropsychological disturbances in humans. Despite their pathogenic potential and high prevalence worldwide, little is known about their cell-specific influences and cerebral host-pathogen interactions in neurotoxocarosis. To address this discrepancy, a co-culture system of viable larvae with murine neuronal (CAD), oligodendrocytal (BO-1) and microglial (BV-2) cell lines has been estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…canis -infection, with concurrent delayed onset in T . cati -infection in terms of clinical symptoms as well as transcriptional and histopathological alterations in the brain [22,24,35,36]. In contrast to the presented study, previously conducted behavioural studies showed no differences in general health of T .…”
Section: Discussioncontrasting
confidence: 84%
“…canis -infection, with concurrent delayed onset in T . cati -infection in terms of clinical symptoms as well as transcriptional and histopathological alterations in the brain [22,24,35,36]. In contrast to the presented study, previously conducted behavioural studies showed no differences in general health of T .…”
Section: Discussioncontrasting
confidence: 84%
“…T. canis eggs were washed and embryonated in tap water at 25 °C for about 4 weeks. Larval hatching was carried out in vitro as described elsewhere 70 . For A. caninum , obtained eggs were incubated in a coproculture for about one week until development of L3.…”
Section: Methodsmentioning
confidence: 99%
“…Worms were scored as dead if their body was completely straight and they did not react when probed with an eyelash. Toxocara catimortality assay: L3 stage larvae for the in vitro assay were prepared as described recently in detail by Heuer et al [52]. A stock solution (5 mg/mL) of the extract was prepared and aliquots were diluted in test medium in a 48-well plate to a final volume of 500 µL per well.…”
Section: In Vitro Assaysmentioning
confidence: 99%